Biological risks for neurological abnormalities associated with hyperbilirubinemia - Brites, D. (2015)
Unconjugated bilirubin (UCB) injury to glial cells leads to the secretion of glutamate and elicits a typical inflammatory response. Release of pro-inflammatory cytokines may influence gliogenesis and neurogenesis, and lead to deficits in learning and memo. - Fundacao para a Ciencia e a Tecnologia (FCT), Lisbon, Portugal. - The authors are grateful to the Fundacao para a Ciencia e a Tecnologia (FCT), Lisbon, Portugal, for their support.